2016
DOI: 10.1149/07516.0243ecst
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ca2+-K+ Image Sensor Using an Inkjet Method and Its Application to Living Cells

Abstract: Ca2+, Na+ and K+ are very important ions in cells in which several ion channels and ion pumps maintain the concentration of their ions. The dynamic analysis of cells requires the monitor of plural ions rather than only one ion. In this paper, we developed simultaneous Ca2+-K+ image sensor. The change in Na+ concentration is hard to detect because of the high concentration (145 mM) in extracellular fluid. The sensing membranes were prepared with plasticized PVC membranes using an inkjet method. The Ca2+-K+ imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…We already reported the fabrication of the Ca 2+ -K + multi-ion image sensor in 2016. 20 In this previous work, we confirmed that the sensor had fast real-time response and high selectivity for target ions through the observation of stimulated HeLa cells, which led to the leakage of K + from intracellular fluid. In order to prove that the multi-ion sensor had wide application potential for both Ca 2+ and K + , a cell event in which Ca 2+ was strongly related to the dynamics was monitored in contrast to the previous observation that was mainly associated with the dynamics of K + .…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…We already reported the fabrication of the Ca 2+ -K + multi-ion image sensor in 2016. 20 In this previous work, we confirmed that the sensor had fast real-time response and high selectivity for target ions through the observation of stimulated HeLa cells, which led to the leakage of K + from intracellular fluid. In order to prove that the multi-ion sensor had wide application potential for both Ca 2+ and K + , a cell event in which Ca 2+ was strongly related to the dynamics was monitored in contrast to the previous observation that was mainly associated with the dynamics of K + .…”
Section: Introductionsupporting
confidence: 64%
“…In our previous examination of the Ca 2+ -K + multi-ion image sensor, 20 both ion selective membranes responded to only the primary ion, and we demonstrated a successful simultaneous imaging of both ions. When the high concentration of Ca 2+ or K + solution was instantly injected into the sensor, each concentration profile changed completely within 1 s. Here, we statistically analyzed the potential responses of all sensing pixels.…”
Section: Evaluation Of Ca 2+ -K + Multi-ion Image Sensormentioning
confidence: 55%
See 1 more Smart Citation
“…Ion image sensor and K + concentration measurement We used the charge transfer type potassium ion image sensor with 128 × 128 pixels (16,384 pixels), which has been developed using a charge-coupled device and complimentary MOS image sensor technologies. 30,31) It has the accessible image area of 4.77 × 4.77 mm 2 with the pixel pitch of 37.3 μm. The size of the sensing region in each pixel is 24.5 × 13.5 μm 2 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…On the other hand, we have also developed multi-ion image sensors which can measure two kinds of ions simultaneously. [52][53][54] Since it was difficult to prepare the two different plasticized PVC membranes by casting, an inkjet printing method was applied to the multi-ion image sensors. An inkjet printer (IJK-200T Microjet) could finely control the printing area and the thickness of the membranes.…”
Section: Chemical Image Sensors Based On Hydrogen Ion Image Sensorsmentioning
confidence: 99%